Describing and Enhancing Collaboration at the Computer - Ken Beatty (The Canadian Network for Innovation in Education (CNIE), 2002)
Computer-based learning materials differ from classroom practice in that they seldom explicitly offer opportunities for collaboration. Despite this, students do collaborate, helping one another through the content and affordances of computer materials. But, in doing so, students meet with challenges. Paradoxically, these challenges can either inspire or discourage learning and second-language acquisition. This paper, based on research with twenty Hong Kong university students in a controlled experiment, evaluates challenges to collaboration at the computer as evidenced by discourse. The students were videotaped and their discourse transcribed and evaluated both qualitatively and quantitatively, according to a set of discourse markers created to describe collaborative, non-collaborative and ambiguous strategies. The paper begins by exploring the differences between collaboration and similar terms such as teamwork and cooperative learning then goes on to define collaboration in the context of computer-assisted learning. It ends by presenting practical suggestions for software designers, teachers and students to enhance collaboration at the computer.